Akses Informasi dan Motif Petani dalam Pemilihan Pasar pada Petani Kopi Giri Senang, Kecamatan Cilengkrang, Kabupaten Bandung - Kusumaningrum, Talitha Syahada; Prasetyo, Agus Subhan; Prayoga, Kadhung (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Coffee was one of the commodities cultivated in Cilengkrang District, Bandung Regency. Each farmer had his own preferences in choosing coffee market related to obtaining information access and his motives. This study aimed to analyze and describe farmers' information access to coffee market and farmers' motives in market selection. This research was conducted from January - March 2023 at Giri Senang Farmers Group, Cilengkrang District, Bandung Regency. The research method used is descriptive qualitative method with Miles and Huberman analysis. There were 15 informants selected by purposive sampling technique that the key informant was the head of Giri Senang cooperative and the main informants were coffee farmers who had access to market information and chose their own market. Primary data was obtained through interviews and observations regarding information access and market selection. Secondary data was obtained from farmer groups, journals and literature related to information access and market selection. The data obtained were analyzed using Miles and Huberman analysis to describe information access and farmers' motives in selecting markets. The results showed that access to coffee market information can be obtained through electronic media such as Instagram, Facebook, or websites as well as through direct information, such as between farmers and shop visitors and fellow farmers. Coffee farmers' motives for choosing markets are as a form of adaptation to online sales and opportunities for wider marketing. The advice given is to maximize the use of social media, expand the target market, increase coordination and supervision in selling products to consumers.